Integrasi Budaya Matanggauk Dalam Materi Pendidikan Agama Islam Di MAN Tolitoli - Lutfi Lutfi (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2025)
The integration of culture into Islamic Religious Education (IRE) materials is an effort to create learning that is contextual and relevant to students' lives. As one of the core subjects in Indonesia's education system, Islamic Religious Education not only serves as a medium for instilling religious values but also functions as an effective means of internalizing humanitarian values, tolerance, and appreciation for cultural diversity. A concrete example of this integration can be found in the incorporation of the values embedded in the Matanggauk tradition, which is still preserved in Tolitoli Regency, Central Sulawesi Province. The Matanggauk culture, which emphasizes values such as deliberation, respect for others, and social solidarity, aligns with the principles of Islamic teachings and has the potential to enrich the learning process in IRE. This article aims to analyze the integration of local cultural values with Islamic teachings as a strategy to strengthen students' character. This study employs a qualitative approach through literature analysis. The findings indicate that Islamic Religious Education can bridge religious values and local culture, and contribute to the development of tolerance, national identity, and an inclusive and applicable understanding of Islam in daily life.